Islands at risk? environments, economies and contemporary change - Connell, John.; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2013)
This book provides a wide-ranging comparative analysis of contemporary economic, social, political and environmental change in small islands, island states and territories, through every ocean. It focuses on those island realms conventionally perceived as developing, rather than developed, in the Caribbean, Pacific and Indian Oceans. John Connell examines the decline of agriculture and the rise of tourism, the problems of urbanization, and the particular role of migration and remittances, within a culture of migration. He seeks to balance economic challenges with environmental threats, notably that of climate change, and social changes with the survival of culture, pointing to awkward and hybrid development futures. This unique study comprehensively balances environmental, social and economic changes to provide a more wide-ranging assessment of sustainability that will be invaluable for academics and postgraduate students on environment and international development courses.
1. Introduction -- 2. Islands and political economies -- 3. The historic core : agriculture and fisheries -- 4. Towards modern economies? -- 5. Urban futures? -- 6. Leaving the islands : international migration -- 7. Environmental change -- 8. Islands at risk?
Includes bibliographical references and index.
Keywords: Islands -- Economic conditions; Islands -- Environmental conditions; Electronic books